Neonatal tactile stimulation at birth in a low-resource setting - Andrea Pietravalle; Francesco Cavallin; Anna Opocher; Stefania Madella; Maria Elena Cavicchiolo; Damiano Pizzol; Giovanni Putoto; Daniele Trevisanuto (BMC, 2018)
Abstract Background Stimulation is the most common intervention during neonatal resuscitation at birth, but scarce information is available on the actual methods, timing and efficacy of this basic step. To evaluate the occurrence, patterns and response to tactile stimulation at birth in a low-resource setting. Methods We reviewed 150 video recordings of neonatal resuscitation at Beira Central Hospital (Beira, Mozambique). Timing, method, duration and response to tactile stimulation were evaluated. Results One hundred two out of 150 neonates (68.0%) received stimulation, while the remaining 48 (32.0%) received positive pressure ventilation and/or chest compressions directly. Overall, 546 stimulation episodes (median 4 episodes per subject, IQR 2-7) were performed. Median time to the first stimulation episode was 134 s (IQR 53-251); 29 neonates (28.4%) received stimulation within the first minute after birth. Multiple techniques of stimulation were administered in 66 neonates (64.7%), while recommended techniques (rubbing the back or flicking the soles of the feet) only in 9 (8.8%). Median duration of stimulation was 17 s (IQR 9-33). Only 9 neonates (8.8%) responded to stimulation. Conclusions In a low-resource setting, stimulation of newly born infants at birth is underperformed. Adherence to international guidelines is low, resulting in delayed initiation, inadequate technique, prolonged duration and low response to stimulation. Back rubs may provide some benefits, but large prospective studies comparing different methods of stimulation are required.